PENGARUH MOTIVASI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PT DAE KYUNG INDONESIA - Sawitri, Ina; Maharani Puteri, Aulia (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
The purpose of this study was to identify and analyze the impact of motivation and competency on employee performance at PT Dae Kyung Indonesia. The type of research used is explanatory research using research methods in the form of data collection using a questionnaire. The data analysis model used is multiple linear regression analysis. Sample selection is done by using saturated samples. The sample consists of 150 respondents who use multi-linear regression analysis. The results of the regression test show that 67.7% of employee performance factors can be explained by Motivation and Competence while the remaining 32.3 are explained by other factors not examined in this study. The F test results indicate that employee performance is positively and significantly impacted simultaneously by the motivation and competence variables with The analysis results indicate that Fcount =157.128 > Ftable = 3.000, which is the same as the value of Fcount = 157.128. The results of the t test show that the motivation variable shows the results of the tcount analysis (8.346) and the compensation variable shows the results tcount (4.476) where ttable (1.960) so partially both variables have a positive and significant effect on employee performance. PT Dae Kyung Indonesia Employee Performance is influenced by Motivation, the dominant variable.